Evolving Banking Sectors: A Literature Review on Current Trends and Challenges - I Gede Putu Suardana (Bata Ilyas Educational Management Review, 2024)
This literature review examines key trends and challenges in the banking industry's evolution, focusing on digital transformation, customer-centric strategies, regulatory compliance, fintech disruptions, and sustainable finance practices. The purpose is to analyze how these elements reshape banking operations and strategy. The research design involved a comprehensive synthesis of existing studies and scholarly works to provide a nuanced understanding of the subject. Findings reveal that digital technologies like AI, ML, and big data analytics are streamlining processes, enhancing decision-making, and fostering innovation in financial products and services. Customer-centric approaches, including personalized services and seamless omnichannel interactions, are becoming pivotal for customer satisfaction and loyalty. The review also highlights the importance of agile risk management frameworks, advanced technologies, and ESG integration in navigating regulatory complexities and ensuring compliance. The implications underscore banks' need to embrace digitalization, sustainability, and regulatory adaptability to stay competitive and meet evolving customer expectations while fostering long-term relationships and trust.